Development Of Islamic Religious Education Books With Contextual Teaching And Learning - hosaini hosaini; Ach Zukin; Mohammad Firdaus (At-Tarbiyat, 2022)
The Contextual Teaching and Learning model is motivated by the low absorption capacity of students in understanding learning; it can be seen from student learning outcomes that are still not optimal, student interest is lacking in motivation, and the learning process is still using teacher-centered. This study aims to improve student learning processes in PAI subjects by compiling textbooks carried out by teachers. The method used is the development method (R and D) at SMP Negeri 1 Banyuputih, . This study shows a significant difference from the previous teaching and learning process seen after the implementation of textbook products with the Contextual Teaching and Learning model. The ability of students to absorb learning is more effective, and students are more active in participating in teaching and learning activities. Students get convenience in understanding the learning material. This learning system can increase students' motivation and learning outcomes, especially in growing students' insight, skills, and attitudes, both in mastering theoretical and pragmatic learning materials.